The Quiet Classroom Game: A Class-Wide Intervention to Increase Academic Engagement and Reduce Disruptive Behavior. Issue 1 (1st March 2016) - Radley, Keith C.; Dart, Evan H.; O'Handley, Roderick D.
Abstract: The current study investigated the effectiveness of the Quiet Classroom Game, an interdependent group contingency using an iPad loaded with a decibel meter app, for increasing academically engaged behavior. Three first-grade classrooms in the southeastern United States, identified as displaying high levels of noise and disruptive behavior, were included in the study. A multiple-baseline design with an embedded ABAB condition sequence was used to evaluate the effect of implementation of the Quiet Classroom Game on academically engaged behavior, disruptive behavior, and classroom decibel level. Implementation of the intervention resulted in large increases in academically engaged behavior, moderate to large reductions in disruptive behavior, and large decreases in classroom noise. Results of social validity checklists administered to teachers and students indicated acceptability and utility of the intervention. Findings of the study suggest that the Quiet Classroom Game may be an effective method for increasing the academically engaged behavior and decreasing the noise and disruptive behavior of first-grade students in a general-education setting.